EFFECTIVITY OF HOUSING REGULATIONS IN INDONESIA TO SUPPORT HOUSING PROVISION FOR LOW INCOME COMMUNITY - Bramantyo Bramantyo (Widyariset, 2012)
The housing problems in Indonesia are related to low-income community such as backlog, sub-standard houseand slum settlement, which are caused by the ineffectiveness of housing regulations. This study was conducted toevaluate the existing housing regulations in order to support housing provision for low-income community. Thestudy was conducted with qualitative approach, by evaluating the Housing Law No. 1/2011, Housing Law No.4/1992, Minister of Housing Regulation No. 3/2007, and Minister of Housing Regulation No. 10/2011. The resultshowed that the new housing law was already accommodated the housing provision for low-income community.Nevertheless, many problems on the implementations were related with the commitment and budget capacity oflocal government. Meanwhile, the limitation standard of low-income community (IDR 2,5 M) was 35% higher thanaverage income of Indonesian people, and the standard price of social house (IDR 25 M) which had standard size(36 m2) was 44 % lower than the market price. These had resulted in the ineffectiveness on the implementation ofthe regulation. The conclusion was that the existing housing regulation was fair effective to support housing provisionfor low-income community, but it was still had weaknesses associated to low-income community limitationstandard and social house standard price.